Creating Connected Identities Among Japanese Company Employees: Learning to be Members of Department Store Work Communities - Creighton, Millie (Culture, 1995)
This paper looks at the meanings, values, and idioms associated with work for members of Japanese permanent employment jobs in a sector of society where this has not previously been well explored - large-retailing organizations. It discusses the boundary markers that distinguish members from outsiders and marginals, and explains the ambiguous identities of part-timers and "helper clerks." The initial year in a Japanese permanent employment job is presented as an intense training period and also a liminal period involving the creation of new social persona and their aggregation into corporate work communities. The paper shows how new department store employees are socialized through training programs, company retreats, and other practices, then discusses the ongoing channeling of employee identities into structured networks of senpai-khai (senior-junior) and entry-year cohort relationships. It also discusses cases of "individualists" who do not fit easily into the company as community ideology. Based on research conducted from the mid-1980s to early 1990s, the paper provides a comparative update to earlier ethnographies of Japanese work in the permanent employment System.